A blockchain-based architecture for secure vehicular Named Data Networks. (September 2020) - Khelifi, Hakima; Luo, Senlin; Nour, Boubakr; Moungla, Hassine; Ahmed, Syed Hassan; Guizani, Mohsen
Highlights: A secure blockchain-based interest forwarding scheme is designed. A reputation-based blockchain caching placement strategy is designed. A lightweight secure neighbor discovery protocol is designed. The designed scheme allows only valid interest packets to be forwarded, and only trust data will be cached and delivered. Simulation results show the feasibility and efficiency. Graphical abstract: Abstract: In vehicular networks, vehicles exchange a massive amount of information aiming at improving people's safety. Most of this information is personal or sensitive in nature, which makes security and privacy indispensable tasks. Named Data Networking is a future Internet architecture that adopts content-based security and in-network caching features to improve content delivery. However, the use of Named Data Networking on top of vehicular networks brings various challenges, especially in security and trust levels. The use of the distributed and control-less in-network caching allows malicious users to use the built-in design to launch attacks at the cache-store. Moreover, a malicious node can serve invalid or unlimited Interests to start an Interest flooding attack. In this paper, we propose a reputation-based Blockchain mechanism to secure both of Interest and Data forwarding plane, and content caching. The simulation results exhibit that our solution forwards only valid Interest and caches only trust content.